E.T. culture: anthropology in outerspaces - Battaglia, Debbora (Duke University Press, 2005)
Insiders' voices in outerspaces / Debbora Battaglia -- Ufology as anthropology : race, extraterrestrials, and the occult / Christopher F. Roth -- Alien tongues / David Samuels -- The license : poetics, power, and the uncanny / Susan Lepselter -- "For those who are not afraid of the future" : raelian clonehood in the public sphere / Debbora Battaglia -- Intertextual enterprises : writing alternative places and meanings in the media mixed networks of Yugioh / Mizuko Ito -- Close encounters of the Nth kind : becoming sampled and the Mullis-ship connection / Richard Doyle -- "Come on, people -- we *are* the aliens. We seem to be suffering from host-planet rejection syndrome" : liminal illnesses, structural damnation, and social creativity / Joseph Dumit.